2011
DOI: 10.1002/ejic.201100848
|View full text |Cite
|
Sign up to set email alerts
|

Cell Cycle Arrest, Cytotoxicity, Apoptosis, DNA‐Binding, Photocleavage, and Antioxidant Activity of Octahedral Ruthenium(II) Complexes

Abstract: Three ruthenium(II) complexes [Ru(dmp) 2+ 2, and [Ru(dip) 2 (dcdppz)] 2+ 3 were synthesized and characterized. The crystal structure of complex 1 was solved by single-crystal X-ray diffraction. This complex crystallizes in the monoclinic system, space group C2/c with a = 18.454(3) Å, b = 44.648 (7)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…The presence of two bromine atoms can enhance the cytoxicity activity of compound 2. Compared 2 with cisplatin (Huang et al, 2011;Cheng et al, 2009), compound 2 showed high cytotoxicity against BEL-7402, Hela, and SKBR-3 cells. The differences in cytotoxicity of compounds 1-4 may be caused by a different log P value.…”
Section: Discussionmentioning
confidence: 98%
“…The presence of two bromine atoms can enhance the cytoxicity activity of compound 2. Compared 2 with cisplatin (Huang et al, 2011;Cheng et al, 2009), compound 2 showed high cytotoxicity against BEL-7402, Hela, and SKBR-3 cells. The differences in cytotoxicity of compounds 1-4 may be caused by a different log P value.…”
Section: Discussionmentioning
confidence: 98%
“…Ruthenium complexes with pyridyl-based ligands are of special interest due to a combination of easily constructed rigid chiral structures and useful photophysical properties. The large, rigid, and multidentate polypyridyl ligands confer shape and chirality to the ruthenium complexes that could be utilized to achieve customized DNA binding properties [88][89][90]. Following the literature reports on the pharmacological benefits of attaching carboxylic acid (COOH) group in coordination complexes [91] Figure 20) [92].…”
Section: Inorganic Ruthenium(ii)mentioning
confidence: 99%
“…The compound NAMI-A, ImH[ trans -RuCl 4 (DMSO)Im] (Im = imidazole), has shown very promising properties in preclinical and phase I clinical trials against lung metastases (Bergamo et al 1999; Morbidelli et al 2003; Rademaker-Lakhai et al 2004; Sava et al 2002; Sava et al 1998) while KP1019, IndH[ trans -RuCl 4 (Ind) 2 ] (Ind = indazole), is effective in ovarian and colon carcinomas (Berger et al 1989; Bratsos et al 2007b; Garzon et al 1987; Hartinger et al 2008; Jakupec et al 2008; Kapitza et al 2005; Seelig et al 1992). In addition, three octahedral Ru (II) complexes were found to induce apoptosis when tested on human hepatoma (BEL-7402 and HepG-2), ovarian (HeLa), and osteosarcoma (MG-63) cancer cell lines (Huang et al, 2011). Most recently, two symmetric ruthenium(II) complexes were found to exert apoptosis on the BEL-7402, HeLa, MG-63 and SKBR (breast) cancer cell lines (Xie et al, 2013).…”
Section: Introductionmentioning
confidence: 99%